‘Mujahadah’ as Moral Education for Students through Hermeneutic Transcendental of "Poison Tree" by William Blake's Poetry - Abdollah, Abdollah; Sulastri, Sulastri; Ratnawati, Ratnawati; Ramdayani, Sri; Mujaddidah, Husnul (Tamaddun Life, 2025)
A literary work of art has the power to directly influence people's thoughts simply by reading a single poem, such as William Blake's "Poison Tree. " The main focus of this study is to explore how any kind of poetry can offer people a way of life, moral education, and new experiences. This research is qualitative in nature and uses content analysis to examine William Blake's poem "Poison Tree. " Hermeneutics, which is often used in literary studies, is regarded as one of the oldest scientific methods and has roots dating back to the time of Plato. This study centers on interpreting the poem to identify the moral values it conveys, using transcendental hermeneutics in the context of the society 5. 0 era, and to explore the types of character education that can be gained. The findings reveal that 'Mujahadah' refers to a struggle against one's passions and the devil, involving a serious effort to overcome these inner conflicts. As stated in a hadith narrated by Bukhari and Muslim, a truly strong person is not one who is physically powerful, but someone who can control their desires even when angry. In the era of disruption brought about by the industrial revolution, transitioning towards society 5. 0, literary works like poetry through the use of internet information technology (IoT) and services (IoS), combined with persuasive spiritual cleansing, light, and wise character education.